Assessing Collegial Collective Leadership and Capacity Building to Strengthen Institutions: Insights from the Indonesian Parliament - Priyo Budi Santoso (Policy & Governance Review, 2026)
This study tested collegial collective leadership in the Indonesian Parliament and its influence on institutional capacity within a coalition-based political system. It ex- plores whether parliamentary leadership effectiveness stems from individual author- ity or from structured, collective mechanisms embedded in partisan dynamics, and adapts the transformational leadership theory to a legislative context. This research employs a qualitative descriptive approach and content analysis, drawing on sec- ondary sources, notably peer-reviewed articles. Data were collected from databases, namely Scopus, Web of Science, and Google Scholar, using keywords such as “colle- gial leadership,” “collective leadership,” “parliament,” “transformational leadership,” and “institutional capacity.” Findings reveal a hybrid leadership model: authority is formally shared among the Speaker and deputy speakers and exercised through com- missions, inter-faction consultations, and plenary consensus, but coalition strength strongly shapes the policy outcomes. Transformational leadership dimensions appear institutionally: idealized influence and inspirational motivation are dispersed across party hierarchies; individualized consideration is limited; and intellectual stimulation, embedded in commission scrutiny and iterative policy review, most strongly enhances the institutional capacity. The study concludes that parliamentary leadership depends on structured deliberation, coordination, and coalition stability rather than on charis- matic authority. Institutional strengthening requires the reinforcement of deliberative procedures, transparent coordination, and systematic learning mechanisms.